2015
DOI: 10.11648/j.cmr.20150404.14
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Malignancies: Analysis of Myelogram Results over 21 Years in Lome Teaching Hospitals

Abstract: Objectives: Determine the frequency of malignancies diagnosed in myelogram seen in hematology services of Campus and Sylvanus Olympio Teaching Hospitals in Lome from 1992 to 2013. Study the epidemiology profile of these diseases. Materials and methods: It was an analytical retrospective study of 469 cases of malignancies diagnosed in 1511 myelograms during 21 years in both teaching hospital of Lome. Results: Blood disorders represent 31.70% of the results of myelogram performed during 21 years in the Teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“… 35–37 In the current study, the result showed that 46.2% of HM was chronic leukemia. This result was in line with the findings reported in India (49.5%) and in Togo (46.7%) 31 , 32 while low findings were reported in India (28.5%) and Bangladesh (18.2%) compared to the present finding. 9 , 30 Chronic leukemia is a broad spectrum of diseases characterized by uncontrolled proliferation and expansion of mature, differentiated cells of the hematopoietic system.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“… 35–37 In the current study, the result showed that 46.2% of HM was chronic leukemia. This result was in line with the findings reported in India (49.5%) and in Togo (46.7%) 31 , 32 while low findings were reported in India (28.5%) and Bangladesh (18.2%) compared to the present finding. 9 , 30 Chronic leukemia is a broad spectrum of diseases characterized by uncontrolled proliferation and expansion of mature, differentiated cells of the hematopoietic system.…”
Section: Discussionsupporting
confidence: 93%
“…This was in line with the findings done in Togo and Bangladesh. 9 , 31 Interestingly, AML is fast-growing leukemia characterized by clonal expansion of immature blast cells in the peripheral blood and bone marrow resulting in ineffective erythropoiesis and bone marrow failure. Furthermore, CML is a slow-growing clonal myeloproliferative disorder characterized by the presence of all stages of myeloid development in the peripheral blood believed to be driven by the aberrant protein tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation